Epithelial Na+ Channel (ENaC) Formed by One or Two Subunits Forms Functional Channels That Respond to Shear Force - Baldin, Jan-Peter; Barth, Daniel; Fronius, Martin (Frontiers in Physiology, 2020)
Canonical epithelial sodium channels (ENaCs) are heterotrimers formed by α, β, and γ ENaC subunits in vertebrates and belong to the Degenerin/ENaC family of proteins. Proteins from this family form mechanosensitive channels throughout the animal kingdom. Activity of canonical ENaC is regulated by shear force (SF) mediating Na+ absorption in the kidney and vascular tone of arteries. Expression analysis suggests that non-canonical ENaC, formed by single or only two subunits, exist in certain tissues, but it is unknown if these channels respond to SF. α, β, γ, and δ ENaC subunits were expressed either alone or in combinations of two subunits in Xenopus oocytes. Amiloride-sensitive currents and the responses to SF were assessed using two-electrode voltage clamp recordings. With the exception of γ ENaC, all homomeric channels provided amiloride-sensitive currents and responded to SF applied via a fluid stream directed onto the oocytes. Channels containing two subunits were also activated by SF. Here, the presence of the γ ENaC subunit when co-expressed with α or δ augmented the SF response in comparison to the αβγ/δβγ ENaC. Overall, we provide evidence that non-canonical ENaC can form channels that respond to SF. This supports a potential function of non-canonical ENaC as mechanosensors in epithelial, vascular, and sensory cells.